CONDUCTIVITY MODULATION IN CR/CRYST.-SI MS STRUCTURE STUDIED THROUGH CURRENT-VOLTAGE AND ADMITTANCE MEASUREMENTS - Ozdemir, Orhan (YILDIZ TECHNICAL UNIV, 2009)
Temperature dependent a. c. capacitance (C) together with ac conductance(G/omega) under various frequency (omega) and d. c. current (I) measurements as a function of bias (V) were employed to investigate both majority and minority carrier injection phenomenon on chromium-p type crystalline silicon (Cr/p-cryst. Si) Schottky diode. This ambipolar transport process behaved differently according to the mentioned techniques: under forward bias, there was a increase in capacitance towards maximum while majority carrier injection proceed from the back electrode. Meanwhile, minority carrier injection from front electrode cause to sharp decrease in measured capacitance from peak position, leading to observation a hump in C-V analysis and followed up tendency due might be interface states and finally end up with constancy. Moreover, shape and peak position of the hump had both frequency and temperature dependency. Remarkably, in the bias range where hump observed, space charge limited current (SCLC) was discerned as the actual enrolled current flow mechanism in I-V measurement, confirming further majority carrier injection. In addition, both dc conductivity and ac conductance behaved similarly. On the other side, reverse current was proportional to square root of reverse bias where constancy of capacitance appeared. These experimental identifications simply imposed the existence of conductivity modulation issue in metal-semiconductor (MS) junction which relies on majority carriers and mostly minority carrier injection is disregarded.
Keywords: Conductivity modulation; minority carrier injection; Engineering